Hubungan Antara Pengetahuan Kesehatan Reproduksi dan Sikap Seksualitas Dengan Perilaku Pacaran Pada Pelajar SLTA - Eny Pemilu Kusparlina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Courtship behavior risk among adolescents, especially students is increasing. During the courtship, students not only get to know each other but they already have kisses even sexual intercourse.This study aims to determine and analyze the relationship between knowledge of reproductive health and sexuality attitude with courtship behavior in high school students at the city of Madiun. This study was an analytic survey with cross sectional approach. This research was conducted at SMAN 6 Madiun, SMAN 4 Madiun, SMKN 2 Madiun and SMKN 3 Madiun. This population was studied at the class X and XI the number of 2209 students, with the sample was 172 students. Sampling tecnic used simple random sampling. Chi-Square is used as bivariate analysis. The results showed reproductive health knowledge of respondents classified as good (83%), sexual attitudes of respondents classified as negative (59%) and the courtship behavior of respondents classified as not at risk (51%). Statistical analysis showed there is a relationship between knowledge of reproductive health (p = 0.002) and sexuality attitude (p = 0.006) with courtship behavior in high school students at the city of Madiun. Keywords: reproductive health knowledge; sexuality attitude; behaviour courtship ABSTRAK Perilaku pacaran yang berisiko dikalangan remaja khususnya pelajar semakin meningkat. Selama berpacaran pelajar tidak hanya berusaha mengenal lawan jenisnya, tetapi sudah sampai berciuman bahkan saling berhubungan seksual. Tujuan penelitian ini untuk mengetahui dan menganalisis hubungan antara pengetahuan kesehatan reproduksi dan sikap seksualitas dengan perilaku pacaran pada pelajar SLTA di Kota Madiun. Penelitian ini menggunakan metode survei analitik dengan pendekatan cross sectional. Penelitian ini dilaksanakan di 4 SLTA Kota Madiun. Populasi dalam penelitian ini adalah pelajar kelas X dan kelas XI sebanyak 2209 siswa, dengan jumlah sampel sebanyak 172 siswa. Pengambilan sampel menggunakan simple random sampling. Analisis bivariat menggunakan Chi-Square. Hasil penelitian menunjukkan pengetahuan kesehatan reproduksi responden tergolong baik (83%), sikap seksualitas responden tergolong negatif (59%) dan perilaku pacaran responden tergolong tidak berisiko (51%). Hasil uji statistik menunjukkan ada hubungan antara pengetahuan kesehatan reproduksi (p=0,002) dan sikap seksualitas (p=0,006) dengan perilaku pacaran pada pelajar SLTA di Kota Madiun. Kata kunci: pengetahuan kesehatan reproduksi; sikap seksualitas; perilaku pacaran